ICT support of the judiciary: The Malaysian experience - Hamin, Zaiton; Othman, Mohd Bahrin; Mohamad, Ani Munirah (2013)
Drawn from an ongoing research which attempts to examine the socio-legal implications of the current adoption of ICT on the delivery of the civil justice system of the High Courts in Malaysia, this paper aims to examine the various ICT applications adopted in the abovementioned courts, and how these applications have improved the delivery of the civil justice system in Malaysia.The research adopts a qualitative method, comprising of the collection of primary data (which involves field work adopting four case studies at the High Courts of West and East Malaysia) and secondary data (which involves library based research).The primary data which have been generated is analysed by using the computer aided qualitative data analysis software ATLAS.ti version 7 prior to reporting of the same.It was found that there are six ICT applications that are currently being adopted by the courts, namely e-filing, case management system, queue management system, recording and transcription, audio and video conference and community and advocates portal.It was further found that these ICT applications have introduced significant improvements to the delivery of the civil justice system in Malaysia, particularly in monitoring the hearing and disposal of civil cases, helping to reduce the backlog of cases and the ageing lists, and helping to increase the disposal rate of cases.The findings will assist the researchers to propose recommendations for the improvement to the practice directions and to propose best practices and code of conduct in implementing ICT in the Malaysian courts.